PENENTUAN JENIS LONGSORAN DI POROS JALAN INDUHA LATAMBAGA KOLAKA SULAWESI TENGGARA - Chaerul, Muhammad; Rasmita, Riza; Anshari, Erwin; Arifin, Asri (Program Studi Magister Pengelolaan Sumberdaya Alam dan Lingkungan Universitas Almuslim, 2023)
The research location is located in Induha Village, Latambaga District, Kolaka Regency, Southeast Sulawesi Province. This study aims to determine the factors controlling landslides, and the types of landslides in the study area. The method used in this research is direct observation in the form of data collection and data collection that is found directly in the field including geological observations, taking rock samples, measuring slopes, and taking documentation of 3 points of landslides. Factors that control the occurrence of landslides in the study area are influenced by controlling factors, namely very steep slopes with a slope of around ± 62o – 67o. Lithological conditions are metamorphic rocks that have undergone changes due to pressure and temperature.